Impact of Global Warming Due to Climate Change on Equatorial Rain-Patterned Regions - Rusmayadi, Gusti; Salawati, Umi; Susanti, Hilda; Adriani, Dewi Erika; Saidy, Akhmad Rizalli (Department of Urban and Regional Planning, Diponegoro University, 2023)
Annual and inter-year climate variability in Indonesia is unique in that not all regions are equal, affecting weather patterns and rainfall. Indonesia's climate is influenced by the global exchange of air mass flows across its territory. Climate patterns in Indonesia can be divided into three main climate patterns, namely monsoon patterns, equatorial patterns, and local patterns based on annual rainfall patterns. The advantage of climate distribution based on rainfall patterns is that the coherence of each region is relatively the same only for applied climate control. This is because when climatic conditions change, newly formed precipitation patterns will prevail. This incident has repeatedly occurred in almost all parts of Indonesia. The analysis used is mean, variance and geo-statistics using secondary data sources from BPS and BMKG in the three regions of East Kalimantan. In the Berau region there is a change in the pattern towards the monsoon winds indicating a rain peak or a pattern of the letter U. In other regions such as Penajam Paser Utara and Paser, an equatorial pattern with two rain peaks remains. Rainfall in the Berau region showed an increase and decrease in the Penajam Paser Utara and Paser regions. The Berau, Paser and Penajam Paser Utara regions will experience a trend of 0.44°C in temperature increases over a 14-year period from 2005-2018, or by 0.03°C per year. Regions that show a shift in rainfall patterns to the equatorial type are particularly sensitive to monsoon winds, which experience rainfall spikes and affect cropping patterns.